Endoscopic Ultrasound‐Guided Angiotherapy for Gastric Varices: A Single Center Experience. Issue 2 (10th December 2018) - Khoury, Tawfik; Massarwa, Muhammad; Daher, Saleh; Benson, Ariel A.; Hazou, Wadi; Israeli, Eran; Jacob, Harold; Epstein, Julia; Safadi, Rifaat
Abstract : There are limited efficacious therapeutic options for management of gastric variceal bleeding. Treatment modalities include transjugular intrahepatic portosystemic shunt, surgical shunts, and endoscopic interventions, including the recent advancement of endoscopic ultrasound (EUS)‐guided coiling. We present a case series of 10 patients with portal hypertension (7 with liver cirrhosis and 3 without cirrhosis), complicated by gastric varices (GV) with bleeding. All cases were treated successfully with EUS‐guided coiling leading to variceal eradication. There were 10 occurrences of minimal self‐limited bleeding at the puncture site during the procedure, and only one occurrence of major bleeding that necessitated cyanoacrylate glue injection for homeostasis. There were no other adverse events within a mean follow‐up time of 9.7 months (range, 1‐28 months). Conclusion: In our series, EUS‐guided angiotherapy was effective for GV eradication with a high safety profile. Abstract : ‐ There is an unmet need for a safe and effective endoscopic therapy in gastric varices ‐ Cyanoacrylate (CYA) glue injection is the recommended first‐line therapeutic modality while TIPS and surgical shunts are mainly used for selected cases ‐ We present a case series of 10 patients with portal hypertension which manifested as GV who were treated successfully with EUS‐guided coiling with variceal eradication